2020
DOI: 10.4025/actascianimsci.v43i1.51158
|View full text |Cite
|
Sign up to set email alerts
|

Milk yield of cows submitted to different levels of olive pomace in the diet

Abstract: The cultivation of olive trees is expanding in Brazil, mainly in Rio Grande do Sul in order to meet the demand for olive oil, the main product of the industrialization of olives. However, from the extraction, there is a significant generation of waste. This residue has high moisture and an appropriate destination is necessary given its environmental and economic importance. The chemical composition of the residue is similar to other products used in animal feed, such as corn silage or sorghum, in relation to D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Several studies utilizing many livestock breeds and species and various levels of inclusion have shown that OC does not adversely affect milk yield and composition when fed in moderate amounts. This was shown in ewes ( (Aljamal et al, 2021); OC at 25% DM; (Vargas-Bello-Pérez et al, 2013); OC at 9.8 and 24.4% DM; (Cabiddu et al, 2004); OC at 10 and 20% DM)), dairy cows ( (Chaves et al, 2020); OC at 5, 10 and 15% DM; (Neofytou et al, 2020); ensiled OC at 10% DM; (Castellani et al, 2017); OC fed at 0.4 kg per day; (Belibasakis, 1984); OC at 20 and 40% DM)), lactating camels ( (Faye et al, 2013); OC at 3% DM), and in dairy goats ( (Keles et al, 2017); OC silage at 10 and 20% DM). Also, (Hadjipanayiotou, 1999) reported that partial replacement of traditional diets (barely hay and straws) with ensiled OC silage did not affect milk yield and fat corrected milk (ewes 6%, goat and cows 4%) of lactating Chios ewes, Damascus goats, and Friesian cows.…”
Section: Lactation Performancementioning
confidence: 86%
“…Several studies utilizing many livestock breeds and species and various levels of inclusion have shown that OC does not adversely affect milk yield and composition when fed in moderate amounts. This was shown in ewes ( (Aljamal et al, 2021); OC at 25% DM; (Vargas-Bello-Pérez et al, 2013); OC at 9.8 and 24.4% DM; (Cabiddu et al, 2004); OC at 10 and 20% DM)), dairy cows ( (Chaves et al, 2020); OC at 5, 10 and 15% DM; (Neofytou et al, 2020); ensiled OC at 10% DM; (Castellani et al, 2017); OC fed at 0.4 kg per day; (Belibasakis, 1984); OC at 20 and 40% DM)), lactating camels ( (Faye et al, 2013); OC at 3% DM), and in dairy goats ( (Keles et al, 2017); OC silage at 10 and 20% DM). Also, (Hadjipanayiotou, 1999) reported that partial replacement of traditional diets (barely hay and straws) with ensiled OC silage did not affect milk yield and fat corrected milk (ewes 6%, goat and cows 4%) of lactating Chios ewes, Damascus goats, and Friesian cows.…”
Section: Lactation Performancementioning
confidence: 86%
“…According to the International Olive Council (2013), Brazil is the third largest importer of olive oil. The country has regions with adequate soil and climatic conditions for the cultivation of olive trees and for this reason, olive growing has been arousing interest in recent years, and in terms of commercial production is still an emerging but expanding agricultural activity (CHAVES et al, 2021).…”
Section: Introductionmentioning
confidence: 99%